UPAYA BADAN KETAHANAN PANGAN KABUPATEN ROKAN HILIR DALAM MENGOPTIMALISASIKAN KETERSEDIAN PANGAN TAHUN 2011– 2013 - Sarpika, Dewi; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Food security is the agricultural sector, which has a strategic role in the development of the regional economy. Kabupaten Rokan Hilir is the largest rice production to reach 50-55% in Riau. Badan Ketahanan Pangan to seek sustainable food security through programs that try stability of rice back. Based on the Law of the Republic of Indonesia Number 18 Year 2012 on Food. Article 41 which reads "Food Diversification is an effort to increase the availability of Food are diverse and are based on potential local resources to meet Food consumption patterns are diverse, nutritionally balanced, safe and fulfilled.The purpose of this research is to answer the problems that exist in the study first, to know efforts the Badan Ketahanan Pangan Kabupaten Rokan Hilir in optimizing availability of food; second, to identify and explain the factors that influence efforts the Badan Ketahanan Pangan Kabupaten Rokan Hilir in optimizing availability of food Year 2011-2013. This type of research is a qualitative research method. The location of this research conducted in Kabupaten Rokan Hilir Province Riau. Data collection techniques including observation, documentation studies and field studies (interview), and analyze the data descriptive.The research showed that the implications of the implementation of optimize food the Local Government Kabupaten Rokan Hilir delegated to the Badan Ketahanan Pangan Kabupaten Rokan Hilir as co-administration the conduct prevention and counseling programs in rice production availability. in the context of what happened today with the rampant land conversion of food to non-food in Rokan Hilir indicate that the lack of local government efforts in the implementation of supervision and counseling in the field of agriculture. In addition, an increase in between institutions counseling is also indispensable in the fight against land conversion to non-edible food in order to achieve an increase in the surplus rice in Riau.Keywords: Badan Ketahanan Pangan, Optimizing Availability of Food, counseling